(untitled) (Comparative & International Education Series, 2021)
This chapter examines student attitudes and issues regarding the rapid pivot to virtual instruction in March 2020. Results indicated that students reported well-prepared and comfortable in the online environment, but the transition and overall life experience of this time left them feeling frustrated, anxious, and worried. They expressed specific concern about the current and future readiness for next courses and careers, amplified by having concerns for their health, the health of others, and their finances. Their responses indicated that open and transparent communication with instructors and about expectations and being included in decision-making about future changes to courses would have provided them with comfort. Training in technology and open communication for educators and students is essential to improving student success and satisfaction during this time of unprecedented change. How to cite: Edens, D., & Kiresich, E. (2022). Student attitudes and experiences with COVID-19: A case of one research university in California. In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 123-138). STAR Scholars. https://starscholars.org/product/global-education/